Uma proposta de personalização de consultas em documentos XML baseada em preferências condicionais - Medeiros, Angélica Felix (2015)
This work presents an extension of the XQuery query language called XQuery-Pref, to support conditional preferences. In order to make transparent to the user executing queries written in language XQuery-Pref, we use a system called XQPref, which is responsible for elicitation of preferences dynamics and the processing of these custom queries. Restrict the scope of this work to XML documents, essential technology for knowledge management and dissemination of data on the Web, that given the information overload, has aroused concern in personalizing query results according to the needs of each user.